2014
DOI: 10.1002/jbmr.2301
|View full text |Cite
|
Sign up to set email alerts
|

The Osteoporosis Treatment Gap

Abstract: Many guidelines for the assessment and treatment of osteoporosis recommend that intervention be considered in men and women who have sustained a fragility fracture.(1) Guidelines in North America (2,3) specifically refer to a prior hip fracture (and spine fracture) as a condicio sine qua non for treatment because of the marked effect of fractures at these sites on both morbidity and mortality. In addition, hip fractures have large economic consequences. For example, hip fractures account for 17% of all osteopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 26 publications
0
87
0
3
Order By: Relevance
“…Given the exponential rise of incidence with age for fractures at many sites [23], and the increasingly elderly demographic globally [2], we are clearly facing a growing burden from osteoporotic fracture in future years. Our findings thus add support to the call for global action to detect, assess and appropriately treat those at high fracture risk, and to close the treatment gap [38] for those who experience a low trauma fracture. Incidence (per 10,000 py) of distal forearm, vertebral and hip fractures in men 1990-2012 in the UK, stratified by 5-year age band.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Given the exponential rise of incidence with age for fractures at many sites [23], and the increasingly elderly demographic globally [2], we are clearly facing a growing burden from osteoporotic fracture in future years. Our findings thus add support to the call for global action to detect, assess and appropriately treat those at high fracture risk, and to close the treatment gap [38] for those who experience a low trauma fracture. Incidence (per 10,000 py) of distal forearm, vertebral and hip fractures in men 1990-2012 in the UK, stratified by 5-year age band.…”
Section: Discussionmentioning
confidence: 52%
“…Indeed in a recent study from the UK using the CPRD only 51.3% of women and 33.6% of men received anti-osteoporosis treatment after a hip fracture, despite this being a marked improvement on 10 years prior where 8.2% of women and 4.1% of men received treatment [37]. This dramatic "treatment gap" has been documented in other populations and should act as a huge incentive to improve identification of treatment of patients for treatment [38]. Interestingly, although there were differences by fracture type, there did not seem to be any overall difference in secular trend between fractures types classified as osteoporotic, compared with those which are not.…”
Section: Discussionmentioning
confidence: 99%
“…The widely publicized issue of ONJ has probably contributed to the decline in the prescription of anti-osteoporosis drugs that has been observed in recent years in various countries, even if their risk-benefit ratio remains favorable [Kanis et al 2014;Solomon et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…According to IOF, the treatment gap in Greece was estimated at 25 % and 31 % for women and men respectively 28 . Furthermore, various studies have shown that of the patients who have had a low trauma fracture just about 20% receive treatment for osteoporosis 29,30 .…”
Section: Discussionmentioning
confidence: 99%